Análise da eficiência das Universidades Federais Brasileiras com enfoque sobre a governança pública - Alves Júnior, Paulo Sérgio Vasconcelos (2019)
The new theories of public administration are observing a gradual change in the paradigm of the relationship between the public power and society, in which the state acts as a mediator of the different public service providers and the autarchic nature of the universities in line with this new model. decentralization. From this emerges the concept of governance, to ensure that these semi-autonomous entities act in line with the interests of society. In this sense, the present work aims to analyze the effect of the degree of governance, measured according to TCU methodology, on the efficiency of Brazilian federal universities. To obtain a robust measure of efficiency, two methodologies were used in parallel: the Stochastic Frontier Approach (SFA) and the Data Envelopment Analysis (DEA), using expenditure data as inputs to the production process and the IGC with product. The results showed that there is room for great potential for higher education improvement by transposing processes from the most efficient to the least efficient universities. There was also a significant geographical distinction in the level of efficiency, with institutions located in more economically developed regions tending to perform better, while those in the northern region tended to rank worse in the calculated ranking. Finally, the results were not consistent with the hypothesis that governance makes institutions more efficient, since, for the two techniques used, no significant statistical relationship was identified between the indicators.